Analisis Kebutuhan Pengembangan Bahan Ajar Modul Instalasi Jaringan Komputer Mata Diklat Komputer dan Jaringan Dasar di Sekolah Menengah Kejuruan - Sulia Ningsih; Nora Agustina (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2021)
The purpose of this study was to determine the need for module development in Learning Computer Network Installation and Basic Networking Courses in Class X SMK TKJ SMK Sentosa Bhakti Baturaja. The type of research used is survey research using interview sheets and questionnaires. The data analysis technique used is descriptive statistics. Based on the results of the study obtained data that 100% of the class X TKJ SMK Sentosa Bhakti Baturaja only use teaching materials in the form of textbooks. 50% of students stated that they needed teaching materials in the form of modules to be used as independent teaching materials for computer network installation learning support. This becomes the basis or consideration for the decision to do the development of module teaching materials in learning Computer Network Installation for Computer and Basic Networking Courses.